Indalecio Prieto and the slow awakening of Spanish public opinion (1924-25) - Sala González, Luis; Galindo Arranz, Fermín (Estudios sobre el Mensaje Periodístico, 2019)
Between November 1924 and June 1925, Indalecio Prieto published a series of editorials in El Imparcial. In this investigation, these contributions will be studied as a whole. Confronted by the military dictatorship of General Primo de Rivera, Indalecio Prieto, inspired by Miguel de Unamuno’s mandate of “We have to make public opinion”, managed to circumvent censorship and transfer the demand of liberties to the newspaper’s readership. His experience as a politician, journalist, and director of the El Liberal newspaper based in Bilbao provide an intuitive, enlightened and modernised interpretation of public opinion. With nearly a decade of hindsight, this collection of texts deserves a second read using later theories concerning the conformation of public opinion. It also allows for a closer look at a strong, critical mind facing a dictatorship, which will culminate with the known Delenda est Monarchia by Ortega and Gasset, and the subsequent emergence of the Second Republic.